Performance of Sharia Mutual Funds Based on Stock Selection Skill and Market Timing Ability in Indonesia - Sahda Marissa; Indah Yuliana (ITB AAS INDONESIA Surakarta, 2023)
The objective of this study is to examine how stock selection and market timing knowledge affect the performance of Islamic mutual funds registered with the Financial Services Authority. The selected sample was 73 (Seventy-three) mixed Islamic mutual funds, money market, fixed income, and stocks in Indonesia during the period of December 2016 to December 2021 which were selected using the purposive sampling method. This study is calculated as a quantitative group with the analysis equipment used is a multiple regession of panel information. The findings show whether knowledge of market timing and stock selection have a favorable impact on mutual fund performance.